Interactive PAI Learning Media Design Using Wordwall and Quizizz to Enhance Student Motivation and Participation - Zahara, Icha Sa’ida; A’yunina, Qurota; Khairah, Afifah (Integrasi: Jurnal Studi Islam dan Humaniora, 2025)
This study aims to develop an interactive learning media design for Islamic Religious Education (PAI) using the Wordwall and Quizizz platforms to enhance student motivation and participation in the learning process. The research method employed is Research and Development (RD), involving needs analysis, media design, expert validation, limited trials, and evaluation. The results indicate that interactive learning media based on Wordwall and Quizizz effectively increase student engagement. Students demonstrate higher learning motivation, active participation, and greater interest in PAI material. These findings highlight the importance of utilizing interactive digital media as an innovative and enjoyable learning strategy.